Regulation of the Yersinia type III secretion system: traffic control - Dewoody, Rebecca; Merritt, Peter M.; Marketon, Melanie M. (Frontiers in Cellular and Infection Microbiology, 2013)
Yersinia species, as well as many other Gram-negative pathogens, use a type III secretion system (T3SS) to translocate effector proteins from the bacterial cytoplasm to the host cytosol. This T3SS resembles a molecular syringe, with a needle-like shaft connected to a basal body structure, which spans the inner and outer bacterial membranes. The basal body of the injectisome shares a high degree of homology with the bacterial flagellum. Extending from the T3SS basal body is the needle, which is a polymer of a single protein, YscF. The distal end of the needle serves as a platform for the assembly of a tip complex composed of LcrV. Though never directly observed, prevailing models assume that LcrV assists in the insertion of the pore-forming proteins YopB and YopD into the host cell membrane. This completes a bridge between the bacterium and host cell to provide a continuous channel through which effectors are delivered. Significant effort has gone into understanding how the T3SS is assembled, how its substrates are recognized and how substrate delivery is controlled. Arguably the latter topic is the least understood; however recent advances have provided new insight, and therefore this review will focus primarily on summarizing the current state of knowledge regarding the control of substrate delivery by the T3SS. Specifically, we will discuss the roles of YopK, as well as YopN and YopE, which have long been linked to regulation of translocation. We also propose models whereby the YopK regulator communicates with the basal body of the T3SS to control translocation.